Work Factors, Employee Performance, and Job Satisfaction in Manufacturing: Faktor Kerja, Kinerja Karyawan, dan Kepuasan Kerja di Organisasi Manufaktur - Hafidz Rizal Ahmad; Misti Hariasih (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative research study aims to investigate the influence of work-related factors on employee performance and job satisfaction within a manufacturing organization. The research objectives encompass exploring the effects of work motivation, work environment, and workload on employee performance, as well as their influence on job satisfaction. The study employed a systematic approach, with a sample of 350 employees from the production department of the organization. Data collection was conducted through questionnaires, and the validity of the data was assessed using Path Analysis. The results reveal that work motivation positively affects performance, along with the significant impacts of work environment and workload on performance. Furthermore, work motivation, work environment, and workload all have direct effects on job satisfaction. The findings also suggest that performance acts as an intervening variable, mediating the relationship between motivation, work environment, workload, and job satisfaction. The implications of this study provide valuable insights for organizations seeking to enhance employee performance and job satisfaction through targeted interventions in work-related factors. Highlights: Work motivation positively influences employee performance and job satisfaction. The work environment and workload significantly impact employee performance and job satisfaction. Employee performance acts as a mediating variable, linking work-related factors to job satisfaction. Keywords: work-related factors, employee performance, job satisfaction, manufacturing organization, targeted interventions